Nano- to macro-scale control of 3D printed materials via polymerization induced microphase separation - Bobrin, Valentin A.; Yao, Yin; Shi, Xiaobing; Xiu, Yuan; Zhang, Jin; Corrigan, Nathaniel; Boyer, Cyrille (Nature communications, 2022)
Although 3D printing allows the macroscopic structure of objects to be easily controlled, controlling the nanostructure of 3D printed materials has rarely been reported. Herein, we report an efficient and versatile process for fabricating 3D printed materials with controlled nanoscale structural features. This approach uses resins containing macromolecular chain transfer agents (macroCTAs) which microphase separate during the photoinduced 3D printing process to form nanostructured materials. By varying the chain length of the macroCTA, we demonstrate a high level of control over the microphase separation behavior, resulting in materials with controllable nanoscale sizes and morphologies. Importantly, the bulk mechanical properties of 3D printed objects are correlated with their morphologies; transitioning from discrete globular to interpenetrating domains results in a marked improvement in mechanical performance, which is ascribed to the increased interfacial interaction between soft and hard domains. Overall, the findings of this work enable the simplified production of materials with tightly controllable nanostructures for broad potential applications. 3D printing allows the macroscopic structure of objects to be easily controlled but controlling the nanostructure of 3D printed materials has rarely been reported. Here, the authors report an efficient and versatile process for fabricating 3D printed materials with controlled nano-scale structural features.